TATA NIAGA PEMASARAN AYAM PEDAGING POLA MANDIRI DI KECAMATAN RASAU JAYA KABUPATEN KUBU RAYA KALIMANTAN BARAT - Angga Permadi Karpriana; Yuli Arif Tribudi (DEPARTMENT OF ANIMAL HUSBANDRY, FACULTY OF AGRICULTURE, UNIVERSITY OF LAMPUNG, 2019)
Livestock is one of the agricultural sub-sectors. Currently, broiler farming business attacks have many attention for researchers to be studied. Trading system becomes an integral part in the entire business activity, so do in broiler farming business. The trading system in broiler farming business is included in the downstream agribusiness sub-system so the farmers are able to be easier in distributing their livestock products to consumers. The aim of this study was to evaluate the trading system of broiler chicken with self-operating model in Rasau Jaya sub-district, Kubu Raya district, West Kalimantan from January to March 2018. Total of 32 livestock keepers and 8 traders were used as samples. Both of the primary and secondary data were collected. This study was performed using descriptive survey method. Snowball sampling method was also applied for sample collection. Trading system of broiler farming business in the studied location is divided into two channels. Channel I consisted of breeders, collectors, consumers, while Channel II consisted of farmers, collectors, retailers, consumers. It could be concluded that channel II was more complex than Channel 1 because in Channel II there was a retailer that had a function as intermediary between traders and consumers. Keywords: Broiler Chicken, Farming Bussiness, Marketing, Self-Operating Model, Trading System